Evaluasi Penerapan Program Teaching Factory terkait Mutu Lulusan SMK di Kabupaten Pasaman Barat (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to evaluate the implementation of the Teaching Factory (TeFa) program in relation to the quality of vocational high school graduates in Pasaman Barat Regency. The research employed a qualitative approach with an evaluative design, utilizing the CIPP (Context, Input, Process, Product) model. Data were collected through observation, in-depth interviews, and documentation at three vocational schools: SMK Negeri 1 Pasaman, SMK Negeri 1 Lembah Melintang, and SMK Negeri 1 Gunung Tuleh. The findings indicate that TeFa implementation has proceeded adequately, although challenges remain in infrastructure, productive teacher competence, and industry partnerships. Context evaluation reveals strong school commitment to TeFa, input evaluation highlights limitations in facilities and teacher training, process evaluation shows variation in implementation across schools, and product evaluation demonstrates improvements in graduates’ technical and soft skills, although work readiness levels are not yet uniform. These results underscore the need for strengthened support from local government and industry to ensure the sustainability of the TeFa program as a strategy for improving vocational education quality.